2012
DOI: 10.15288/jsad.2012.73.216
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Dropout in the First 3 Months of 12-Step Residential Drug and Alcohol Treatment in an Australian Sample

Abstract: Predicting dropout in the first 3 months of 12-step residential drug and alcohol Predicting dropout in the first 3 months of 12-step residential drug and alcohol treatment in an Australian sample treatment in an Australian sample

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 65 publications
0
39
1
7
Order By: Relevance
“…[105][106][107][108]). This evidence might be ascribed to some patient characteristics such as age and cognitive deficits that represented robust risk factors across several clinical trials with different orientations (for a meta-analytic review see: [53]).…”
Section: Discussionmentioning
confidence: 99%
“…[105][106][107][108]). This evidence might be ascribed to some patient characteristics such as age and cognitive deficits that represented robust risk factors across several clinical trials with different orientations (for a meta-analytic review see: [53]).…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to treatment dropout. A study indicated that poor psychological well-being was a strong predictor of dropping out from TCP (20). Some KIs highlighted the roles of some psychological services such as training in life skills.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies report drop-out rates ranging from 21.5-43% in detoxification [89,90] outpatient treatment 23-50% [91,92], inpatient treatment 17-57% [93] and substitution treatment 32-67.7% [94,95]. A meta-analysis of psychotherapy found a dropout rate between 19 and 47% [96].…”
Section: Positive Outcomesmentioning
confidence: 99%